VD_FINDINFO Décision / 2014 / 191 vom 23. Dezember 2013 - VD Tribunal cantonal (2013)
CLASSEMENT DE LA PROCÉDURE, PLAIGNANT, LÉSÉ, DÉPENS | 319 CPP (CH), 420 CPP, 429 al. 1 let. a CPP (CH), 432 CPP (CH)